Selected letters of Walt Whitman - Whitman, Walt, 1819-1892.; Miller, Edwin Haviland (Iowa City, IA : University of Iowa Press, 1990)
There has never been an edition of the selected letters of Walt Whitman, a remarkable fact considering how accustomed we are to becoming acquainted with major writers through their letters. Now Edwin Haviland Miller, editor of the six-volume collected writings of Whitman, has used his intimate knowledge of the "good gray poet's" correspondence to produce this revealing selection of 250 letters, introduced and annotated concisely and evocatively. Whitman in these letters is simple, direct, colloquial, adding a counterpoint to his artistic voice and persona as a poet.
Acknowledgments; Preface; Introduction; 1840 -- 1841; 1842 -- 1860; 1861 -- 1865; 1866 -- 1873; 1873 -- 1881; 1881 -- 1889; 1890 -- 1892; Notes; Index of Whitman's Correspondents
Includes index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Includes bibliographical references and index.
Keywords: Whitman, Walt, -- 1819-1892 -- Correspondence; Whitman, Walt, -- 1819-1892; Whitman, Walt; Poets, American -- 19th century -- Correspondence; Poètes américains -- 19e siècle -- Correspondance; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- Poetry; LITERARY CRITICISM -- American -- General; Poets, American; 1800-1899; Personal correspondence